Homeopathy - what are the active ingredients? An exploratory study using the UK Medical Research Council's framework for the evaluation of complex interventions - Weiss Marjorie; Thompson Trevor DB (BMC, 2006)
Abstract Background Research in homeopathy has traditionally addressed itself to defining the effectiveness of homeopathic potencies in comparison to placebo medication. There is now increasing awareness that the homeopathic consultation is in itself a therapeutic intervention working independently or synergistically with the prescribed remedy. Our objective was to identify and evalute potential "active ingredients" of the homeopathic approach as a whole, in a prospective formal case series, which draws on actual consultation data, and is based on the MRC framework for the evaluation of complex interventions. Methods Following on from a theoretical review of how homeopathic care might mediate its effects, 18 patients were prospectively recruited to a case series based at Bristol Homeopathic Hospital. Patients, who lived with one of three index conditions, were interviewed before and after a five visit "package of care". All consultations were recorded and transcribed verbatim. Additional data, including generic and condition-specific questionnaires, artwork and "significant other" reports were collected. Textual data was subject to thematic analysis and triangulated with other sources. Results We judged that around one third of patients had experienced a major improvement in their health over the study period, a third had some improvement and a third had no improvement. Putative active ingredients included the patients' "openness to the mind-body connection", consultational empathy, in-depth enquiry into bodily complaints, disclosure, the remedy matching process and, potentially, the homeopathic remedies themselves. Conclusion This study has has identified, using primary consultation and other data, a range of factors that might account for the effectiveness of homeopathic care. Some of these, such as empathy, are non-specific. Others, such as the remedy matching process, are specific to homeopathy. These findings counsel against the use of placebo-controlled RCT designs in which both arms would potentially be receiving specific active ingredients. Future research in homeopathy should focus on pragmatic trials and seek to confirm or refute the therapeutic role of constructs such as patient "openness", disclosure and homeopathicity.